Potassium buffering capacity and corrective potassium fertilizer recommendations in soils from Southern Brazil - Abelino Anacleto de Souza Junior; Gilmar Luiz Mumbach; Édila Almeida; Douglas Luiz Grando; Luciano Colpo Gatiboni; Gustavo Brunetto; Paulo Roberto Ernani (Revista Brasileira de Ciência do Solo, 2022)
ABSTRACT Soils with low potassium (K) availability require corrective fertilization for grain crops. The recommended rate to increase K availability up to the critical level depends on the soil K buffering capacity (KBC). This study aimed to quantify the KBC and recalculate the rates necessary to reach the K critical level in 23 soils from Southern Brazil. Soil samples were incubated with six K rates, that were thus grouped according to CECpH7.0: below 7.5 cmolc dm-3 (0, 30, 60, 90, 120 and 180 kg K2O ha-1); from 7.6 to 15 cmolc dm-3 (0, 30, 60, 120, 180 and 240 kg K2O ha-1) and from 15.1 to 30 cmolc dm-3 (0, 30, 60, 120, 240 and 360 kg K2O ha-1). The soil test K (STK) was extracted by Mehlich-1 and the fertilizer rates necessary to increase the STK by 1 mg dm-3 were quantified. The KBC values were correlated with a suite of soil testing metrics. The relationship between the cation exchange capacity (CECpH7.0) and KBC was modeled, and a linear-plateau equation presented the best fit. The K rates were calculated using the following equation: K rate = ( Critical Level − S T K ) × K B C and were compared with the current rate indicated by the Local Soil Fertility Committee. The K fertilizer rates by KBC were about 2.5 times higher than the values currently indicated, and the largest differences were observed in soils with low STK and high CECpH7.0.